Molecular phylogenetic analyses and micromorphology reveal placement of the enigmatic tropical discomycete Polydiscidium in Sclerococcum (Sclerococcales, Eurotiomycetes) - Haelewaters, Danny; Stallman, Jeffery K; Henkel, Terry W; Aime, M Catherine (Mycologia, 2022)
Polydiscidium is an enigmatic, monotypic, and rarely reported genus of Ascomycota of uncertain placement. The morphologically unique Polydiscidium martynii grows on dead wood and forms compound ascomata composed of thick, black, gelatinous somatic tissue that branches out from a common base. Multiple apothecia are located on the branches, mostly toward the tips, and are composed of 8-spored asci and paraphyses embedded in a gelatinous matrix that turns blue in Melzer's reagent. The species was previously known from only three collections from Guyana (holotype), Trinidad, and the Democratic Republic of the Congo and no sequences exist. Due to its peculiar morphology, taxonomic affinities of Polydiscidium have been debated, with different authors having placed it in Helotiaceae, Leotiaceae, or Leotiomycetes incertae sedis. Recent collections of this species resulting from long-term field work in Guyana and Cameroon led us to revisit the morphology and phylogenetic position of this fungus. Newly generated sequences of P. martynii were added to an Ascomycota-wide six-locus data set. The resulting phylogeny showed Polydiscidium to be a member of order Sclerococcales (Eurotiomycetes). Next, a four-locus (18S, ITS, 28S, mtSSU) phylogenetic reconstruction revealed that Polydiscidium is congeneric with Sclerococcum. A new combination is proposed for this species, Sclerococcum martynii. Micromorphological features, including the gelatinous hymenium composed of asci with amyloid gel cap and septate brown ascospores, are in agreement with Sclerococcum. New combinations are proposed for two additional species: Sclerococcum chiangraiensis and S. fusiformis. Finally, Dactylosporales is considered a later synonym of Sclerococcales.
Keywords: multilocus phylogeny; 3 new taxa; Phylogeny; systematics; Ascomycota; Guiana Shield; Guyana; Sclerococcaceae; fylogeneze; spory hub; rare fungi; taxonomy; dřevo; Cameroon; Wood; Spores, Fungal